2017
DOI: 10.1111/bld.12198
|View full text |Cite
|
Sign up to set email alerts
|

Mental capacity to consent to research? Experiences of consenting adults with intellectual disabilities and/or autism to research

Abstract: Accessible Summary• The NHS Constitution states that all patients should have opportunity to take part in approved research • This study asked clinical researchers how they include people with intellectual disabilities and/or autism in research • Many barriers were identified that relate to making mental capacity judgements • Many researchers agreed new resources that support consent and capacity judgements for research would be helpful and gave some ideas about what could help. AbstractBackground: Adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
1
Order By: Relevance
“…Given the subjective nature of QoL it may be, prima facie, that proxy‐reports cannot be a valid substitute for a first person rating. However, adults with intellectual disability are frequently excluded from research due to issues with obtaining valid informed consent [Hamilton et al, ]. As such, this excludes a portion of the autism community from being recognized in QoL research.…”
Section: Discussionmentioning
confidence: 99%
“…Given the subjective nature of QoL it may be, prima facie, that proxy‐reports cannot be a valid substitute for a first person rating. However, adults with intellectual disability are frequently excluded from research due to issues with obtaining valid informed consent [Hamilton et al, ]. As such, this excludes a portion of the autism community from being recognized in QoL research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals present with different levels of learning disability, it is associated with other disorders (Smith & Matson, ) and some present with CB. Due to the complexity of the issue and perceived difficulty with gaining consent for participation in studies, there is emerging evidence to suggest that people with a learning disability and autism spectrum disorder (ASD) are specifically excluded from healthcare research (Hamilton et al, ). In addition, the study of sensory integration (Watling & Hauer, ) is a new and developing area, which is also under‐researched amongst adults with learning disability (May‐Benson & Kinnealey, ).…”
Section: Introductionmentioning
confidence: 99%
“…The disconnect between established approaches to providing care for populations who lack capacity, and approaches to the design and conduct of trials involving them, creates a conflict between the care and clinical trial paradigms that acts as a barrier to their inclusion [60]. Person-centred approaches to health care focus on flexibility and relationality through treating people as individuals, respecting their rights as persons, building mutual trust and understanding, and developing relationships [61].…”
Section: Lack Of 'Person-centred' Approaches In Trialsmentioning
confidence: 99%
“…In stark contrast, there is little explicit attention paid to the concept of person-centredness in trials involving these same populations [62]. Researchers conducting trials with adults with intellectual disabilities and/or autism identified the need to embrace a range of person-centred approaches, particularly around consent processes, to ensure trials are more inclusive [60]. Adopting these approaches, particularly the tailoring of information provision and consent processes, the use of decision aids and visual aids to improve cognitive accessibility, and revisiting consent after data collection, are key to successful trials involving adults lacking capacity [60].…”
Section: Lack Of 'Person-centred' Approaches In Trialsmentioning
confidence: 99%
See 1 more Smart Citation